DISTRIBUIÇÃO E BIODIVERSIDADE DE PEIXES RECIFAIS BRASILEIROS: EXPLORANDO HABITATS BENTÔNICOS DA ZONA MESOFÓTICA - Pimentel, Caio Ribeiro (2021)
Reef fish are efficient models for carrying out ecological studies at relatively small spatial and temporal scales, allowing us to understand how some environmental characteristics structure their communities. In this sense, depth and benthic habitat (e.g., reefs, rhodolith beds and macroalgae) are one of the most important environmental characteristics. Despite the uniqueness and vulnerability of Brazilian reef fish communities, we still know little about the biodiversity and distribution patterns of species in mesophotic habitats (which occur between 30 and 150 m deep). Therefore, the main objective of this thesis was to analyze the composition and structure of fish assemblages in different Brazilian oceanic islands, aiming to understand mainly how depth and habitats act structuring these assemblages. Baited remote underwater stereo-video systems (stereo-BRUVS) were used to explore diverse benthic habitats along a wide depth gradient (~10 to 90 m) at Trindade Island, Fernando de Noronha Archipelago and Saint Peter and Saint Paul’s Archipelago (SPSPA), as well as on the east coast of Brazil. Unexpectedly, in SPSPA reef fish assemblages were not structured according to the depth gradient. Species distribution was more associated with up and down-welling events, which drastically change the temperature and influence the vertical movement of fishes along the reef. Furthermore, several species were recorded in both pelagic and reef environments, suggesting ecological connections between them, through the flux of matter and energy. In turn, the Trindade Island insular shelf comprises a mosaic of interconnected benthic habitats, which differ in richness, abundance and biomass of fish assemblages. Reefs showed greater richness and abundance, as well as a greater proportion of exclusive species, followed by rhodolith beds, macroalgae beds, and sandy bottoms. Depth was considered an intrinsic characteristic of habitats, as they are not continuously distributed along the bathymetric gradient of the insular shelf. These environmental characteristics, therefore, act in synergy in the structuring of fish assemblages. Regarding biodiversity, using stereoBRUVS it was possible to analyze the composition and abundance of shark species in these two oceanic islands, including a species considered locally extinct in SPSPA. In Fernando de Noronha, stereo-BRUVS accounted for three new records. These results reinforce the need for integrated management strategies that include euphotic and mesophotic, benthic and pelagic habitats, reefs or non-reefs, aiming at the conservation of biodiversity, ecological functions and connectivity in marine environments.